The Effect of FOMO on Impulse Buying with Emotional Marketing as a Mediation Variable on TikTok Live - Amanda Amanda; Dewi Santika (Jurnal EMT KITA, 2026)
This study investigates the impact of Fear of Missing Out (FOMO) on impulsive purchases, with emotional marketing as a mediating variable, among students in Pontianak who shop via TikTok Live. A quantitative method with an explanatory design was applied. Primary data were collected via a questionnaire distributed to 150 students selected through purposive sampling based on having shopped online, being exposed to emotional marketing, and being at least 17 years old. Data analysis used structural equation modeling (SEM) with AMOS. The findings reveal that FOMO has a positive and significant impact on impulsive buying. FOMO also has a positive and significant impact on emotional marketing. Furthermore, emotional marketing was found to have a positive and significant influence on impulsive buying. Sobel test results confirm that emotional marketing significantly mediates the influence of FOMO on impulsive buying. These findings suggest that the increase in impulsive purchasing behavior among students in Pontianak on TikTok Live is more influenced by the fear of missing out on trends, which is amplified through emotional marketing strategies such as urgency, exclusivity, and social validation. This study suggests that businesses need to effectively adopt and implement emotional marketing strategies to amplify FOMO's impact on consumers' spontaneous purchasing decisions.